2002
DOI: 10.1176/appi.ajp.159.10.1642
|View full text |Cite
|
Sign up to set email alerts
|

Drug Addiction and Its Underlying Neurobiological Basis: Neuroimaging Evidence for the Involvement of the Frontal Cortex

Abstract: Objective-Studies of the neurobiological processes underlying drug addiction primarily have focused on limbic subcortical structures. Here the authors evaluated the role of frontal cortical structures in drug addiction.Method-An integrated model of drug addiction that encompasses intoxication, bingeing, withdrawal, and craving is proposed. This model and findings from neuroimaging studies on the behavioral, cognitive, and emotional processes that are at the core of drug addiction were used to analyze the invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

104
1,755
7
79

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,368 publications
(1,945 citation statements)
references
References 105 publications
104
1,755
7
79
Order By: Relevance
“…Similar neural changes may be responsible for the cognitive impairments observed in humans with drug addiction (Goldstein and Volkow, 2002;Pfefferbaum et al, 1998;Bechara, 2005;Franklin et al, 2002;Jentsch and Taylor, 1999;Rogers and Robbins, 2001).…”
Section: Discussionmentioning
confidence: 87%
“…Similar neural changes may be responsible for the cognitive impairments observed in humans with drug addiction (Goldstein and Volkow, 2002;Pfefferbaum et al, 1998;Bechara, 2005;Franklin et al, 2002;Jentsch and Taylor, 1999;Rogers and Robbins, 2001).…”
Section: Discussionmentioning
confidence: 87%
“…Based upon our previous findings in alcohol and opiate dependence for the [ 11 C]Ro15‐4513 PET analysis, we selected right hippocampus and NAc as a priori ROIs, and we chose two additional a priori ROIs based upon their established role in impulse control: OFC and amygdala (Goldstein and Volkow 2002; Jentsch and Taylor 1999; Ko et al 2015; Nikolova et al 2016). As previous work (Clark et al 2012; Michalczuk et al 2011) has shown that NU, as a mood‐related subgroup of impulsivity, is most strongly associated with GD, we chose to test for correlations between UPPS‐P NU and a priori selected brain regions.…”
Section: Methodsmentioning
confidence: 99%
“…Within the CNS, ACh is involved in motor behaviors, modulating the behavioral states associated with incoming information such as emotional tone, motivation, and arousal (Mesulam, 1996), as well as complex cognitive processes such as attention, learning, and memory (Sarter et al, 2003). Limbic and paralimbic regions of the CNS contain the highest density of ACh innervations in the brain (Mesulam, 1996) and are thought to be most relevant to the process of addiction (Bonson et al, 2002;Childress et al, 1999;Goldstein and Volkow, 2002). These regions include the ventral striatum (including the NAc), dorsal striatum, VTA, substantia nigra (SN), amygdala, hippocampus, and prefrontal cortex (PFC) (Lautin, 2001;Papez, 1995).…”
Section: Overview Of the Central Cholinergic Systemmentioning
confidence: 99%